Cancer prevention by adult‐onset calorie restriction after infant exposure to ionizing radiation in B6C3F1 male mice. Issue 5 (11th February 2014) - Shang, Yi; Kakinuma, Shizuko; Yamauchi, Kazumi; Morioka, Takamitsu; Kokubo, Toshiaki; Tani, Shusuke; Takabatake, Takashi; Kataoka, Yasushi; Shimada, Yoshiya
<x xml:space="preserve">Abstract</x> Children are especially sensitive to ionizing radiation and chemical carcinogens, and limiting their cancer risk is of great public concern. Calorie restriction (CR) is a potent intervention for suppressing cancer. However, CR is generally not appropriate for children. This study, therefore, examined to see if adult‐onset CR influences the lifetime cancer risk in mice after early‐life exposure to ionizing radiation. Infant male mice (1‐week‐old) were exposed to 3.8 Gy X‐rays, fed a control 95 kcal/week or CR 65 kcal/week diet from 7 weeks of age (adult stage), and their lifespan and tumor development were assessed. Irrespective of CR, X‐rays shortened lifespan by 38%, and irrespective of irradiation CR extended lifespan by 20%. Thymic lymphoma (TL) and early‐occurring non‐TL were induced by radiation. The liver and Harderian gland were more susceptible to radiation‐induced tumors than the lungs and non‐thymic lymphoid tissues (late occurring). CR reduced the risk of hepatocellular carcinoma, late‐occurring non‐TL, lung tumor, Harderian tumor, and hemangioma but had less impact on TL and early‐occurring non‐TL. Most notably, the effects of X‐rays on induction of lung tumors, late‐occurring non‐TL and hemangioma were essentially canceled by CR. The ability of CR to prevent late‐occurring tumors was the same for non‐irradiated and irradiated mice, indicating that the mechanism by which CR influences cancer is independent of irradiation. Our results indicate that adult‐onset CR significantly inhibits late‐occurring tumors in a tissue‐dependent manner regardless of infant radiation exposure.